Treatment of perniosis with oral tadalafil, pentoxifylline or prednisolone A therapeutic comparative study - sharquie, Khalifa E.; Salman, Husam Ali; Noaimi, Adil A. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: perniosis is a common dermatological problem. Different modalities of treatment are available with conflicting results and no single effective therapy is universally accepted.Objective: To evaluate the effectiveness of oral tadalafil and compare it with pentoxyfylline or prednisolone in treatment of perniosisPatients and methods: This was a therapeutic comparative trial conducted in the department of Dermatology, Baghdad Teaching hospital, Baghdad, Iraq between November 2011 and March 2014.Fifty eight patients with perniosis were enrolled in this study, and divided into 3 groups. Group (A) comprised 19 patients who received oral tadalafil (5 mg once daily); group (B) comprised 18 patients who received pentoxifylline tablet (400 mg three times daily) and group (C) included 21 patients who received prednisolone 15 mg twice daily. The treatment duration was 2 weeks. All patients did not receive any treatment before the study. A severity score was proposed taken in consideration the number of finger/ toes, type of lesion, coldness, cyanosis and itchingResults: Forty seven patients completed the study. Their ages ranged from 13-43 with a mean ± SD of 22.38 ±6.99 years. Thirty three patients were females (70.21%) and 14 were males (29.79%).The percentage of improvement was 50.65, 44.16 and 31.51% for the groups A, B and C respectively.Conclusion: Tadalafil has a superior effect over pentoxyfylline. The latter has a better effect than prednisolone.